Environmental protection type cool storage medium - WEIMIN ZHANG; ZENGRONG TANG; JUEMIN ZHANG (2004)
An environment protection type cold accumulating medium for refrigerator, domestic cold pad and medical ice bag, etc. contains natural or synthetic starch or carboxymethyl cellulose or sodium alginate, 1,2-propanediol or propanetriol as antifreezing agent, sodium chloride or potassium chloride or sodium sulfate, and water. Its advantages are no damage to human body, and no environmental pollution. 家庭日常生活中使用的环保型储冷介质，组成成分有：天然或半合成天然高分子材料--淀粉、羧甲基纤维素或海藻酸钠；抗冻剂1，2-丙二醇或丙三醇；无机盐氯化钠、氯化钾或硫酸钠；水。这种储冷介质的优点是其组成成分对人体无毒无害，不污染环境；存放于家庭冰箱冷冻室中，24小时以上不结冻，无冰渣颗粒；能方便地对各种饮料、酒类和固态食品冷却降温；也可用于家庭降温凉爽垫、医用冰敷袋及药品的降温保质。